PENGEMBANGAN E-MODUL KIMIA BERBASIS METAKOGNISI MENGGUNAKAN APLIKASI EDMODO - Shiba Meike Indira; Agus Sundaryono; Rina Elvia (ALOTROP, 2020)
Metacognition is one of the factors that influence academic achievement, so it is very important in each student's learning activities. The objective of this research was to find out the level of feasibility and students response to E-chemistry-based metacognition using the edmodo application as teaching material to train students' knowledge and metacognition experience of students of the XI MIPA class of SMA Negeri 2 Kota Bengkulu T/P 2018/2019 on acid-base material. This research was an Research & Development (R&D) using the 4D development model limited to the development stage. The development of this emodule uses the edmodo application and in its using the flipped classroom learning model. Information worthy of being used as teaching of expert assessments and student responses to limited testing and field testing. The assessment of e-module was carried out by media experts, it was obtained that e-module is very feadible to use without revision with an evaluation percentage of 93%, an assessment by material experts and practitioners ( chemistry teacher) was very feasible to use without revision with an evaluation percentage of 92%, then the metacognition –based was assessed by material experts was obtained e- module was very feasible to use without revision with a percentage of 88% so that based on the results of expert evaluations, e-module could testedon a limited trial class and field trial. Sample selection in limited trials and field trials obtained from the results of normality tests conducted on january 3,2019 from the popuation of class XI Mipa A- XI Mipa F as many 190 students obtained 15 students XI Mipa C as samples ini limited trials and 31 students XI Mipa E in the field trial. Response of students in limited trials carried out on january 14,2019 and field tests on january 30,2019 amounting to 86% and 84% this shows that the use of emodules is very teasible to use as teaching materials and obtained information that e-module can train the ability of metacognition students of the XI MIPA SMA Negeri 2 Kota Bengkulu T/P 2018/2019 in particular the knowledge and metacognition experience of student from less trained to being trained.